Determinant Factors of Low Cognitive, Motoric and Language Performance of HIV-Infected Children - Putu Indah Budiapsari; I Nyoman Supadma (Fakultas Kedokteran UPN Veteran Jakarta Kerja Sama KNPT, 2022)
The Effects of HIV infection on children’s physical growth, psychological health, and neurodevelopment are essential. We aimed to find out the determinants factor of low cognitive, motoric and language performance of HIV-infected children. This study examined 68 HIV-infected children ranged 0-36 months. Cognitive, motoric and language were assessed using Cognitive Adaptive Test (CAT) and Clinical Linguistic and Auditory Milestone Scale (CLAMS) score which are components of of Capute Scale. Data was analyzed using cross tab, and significant Pearson chi-square (p < 0.05) was used to identify the determinant factors. The result showed that CD4 level, length of antiretroviral treatment, age, stage of HIV infection, socio economic status, and family income were determinant factors of low cognitive, motoric and language performance of HIV infected children. It can be concluded that cognitive, motoric and language were affected by CD4 level, length of antiretroviral treatment, age, stage of HIV infection, socio economic status, and family income.